Breast cancer risk and hormone replacement therapy among BRCA carriers after risk-reducing salpingo-oophorectomy. (May 2021) - Michaelson-Cohen, Rachel; Gabizon–Peretz, Shira; Armon, Shunit; Srebnik-Moshe, Naama; Mor, Pnina; Tomer, Ariela; Levy-Lahad, Ephrat; Paluch-Shimon, Shani
Abstract: Introduction: BRCA1/BRCA2 mutation carriers often undergo risk-reducing salpingo-oophorectomy (RRSO) before natural menopause, raising the issue of hormonal replacement treatment (HRT) use. There is conflicting evidence on the effect of HRT on breast cancer (BC) risk, and there are limited data on risk based on age at exposure. In the general population, HRT users have an increased BC risk (hazard ratio = 1.34). We assessed the impact of short-term HRT use on BC risk among healthy BRCA1/2 mutation carriers, with emphasis on age at exposure to HRT. Methods: A retrospective cohort of 306 consecutive healthy BRCA1/2 mutation carriers who had undergone RRSO was followed up for a mean of 7.26 years. We compared BC incidence over time in carriers who received HRT with that in those who did not receive. Results: Thirty-six of the carriers were diagnosed with BC, 20 of 148 patients (13.5%) in the HRT group compared with 16 of 155 (10.3%) in the non-HRT group (odds ratio [OR] = 1.4, 95% confidence interval [CI] = 0.7–2.7). In women who were aged 45 years or younger at RRSO, HRT did not affect BC rates. However, in those older than 45 years at RRSO, BC rates were significantly higher in HRT users than in non-users (OR = 3.43, p < 0.05, 95% CI = 1.2–9.8). Conclusions: In BRCA1/BRCA2 carriers in this study, short-term post-RRSO HRT use was associated with a threefold risk of BC in carriers older than 45 years. These results suggest that risk may be related to time of exposure to HRT around the natural age of menopause, even among BRCA1/2 carriers. Further studies are needed for validation and to guide future recommendations. Highlights: Hormonal replacement treatment (HRT) appears safe in BRCA carriers under 45 years old. HRT was associated with a tripled breast cancer risk for BRCA carriers over 45 years. HRT did not affect age at breast cancer diagnosis and time from oophorectomy till diagnosis.